Assessment on the Antimicrobial Activity of Lactiplantibacillus plantarum SU-KC1a against Listeria monocytogenes ATCC-7644 - Timothy, Michael; Samantha, Ariela; Sugata, Marcelia; Tan, Tjie Jan; Jo, Juandy (Universitas Atma Jaya Yogyakarta, 2025)
Lactobacillus species are particularly noteworthy due to their ability to synthesize a variety of antimicrobial substances, including organic acids and bacteriocins. Lactiplantibacillus plantarum SU-KC1a, a member of the genus of Lactobacillus, had been previously isolated from human breast milk by our group. A preliminary in silico investigation had identified that Lpb. plantarum SU-KC1a possessed genes responsible for plantaricin, which is a type of bacteriocin produced by Lpb. plantarum strains. This study therefore aimed to assess the antibacterial activity of Lpb. plantarum SU-KC1a against pathogenic Listeria monocytogenes ATCC-7644 and to induce the biosynthesis of plantaricin by Lpb. plantarum SU-KC1a through co-culture with L. monocytogenes ATCC-7644 as the inducer strain. Our results showed that the cell-free supernatants from both co-culture and monoculture of Lpb. plantarum SU-KC1a exhibited a modest antibacterial activity against L. monocytogenes ATCC-7644. However, it was further determined that the inhibitory effect was not due to the production of plantaricin. Instead, it was primary attributed to the production of organic acids, which decreased the pH and inhibited the growth of L. monocytogenes ATCC-7644. In conclusion, our study demonstrated that Lpb. plantarum SU-KC1a could exert a modest antibacterial activity towards L. monocytogenes ATCC-7644, but not through the induction of plantaricin.